Evaluation of the Library Information System of the facuty of Philosophy in Zagreb, Croatia in the Context of Education in the Electronic Environment - Lasić-Lazić, Jadranka (Array, 2004)
Stating that the knowledge is the most important resource, and that the knoweldge is the mere essence of the value materialised in the produced materials, authors research in what way has the library information system accepted proposed changes and what changes has it accomplished in the new educational environment. The data for the system analysis was gathered by surveying libraries